Izbrani vidiki celovitosti površine aluminijeve zlitine pri običajni in obdelavi z velikimi hitrostmi: Spremembe mikrotrdote in hrapavosti površine - Vaněček, David (Strojniški vestnik, 2003)
This paper deals with the quality and integrity of the surface produced during aluminium-alloy high-speed machining (HSC). Carbide type- K tools were used in this study. The results of the microhardness and surface-roughness analyses are presented. The microhardness measurements were conducted beneath the machined surface. The analyses of the surface produced are presented in a range of surface-roughness parameters. Relations between microhardness variations and surface roughness were obtained from the analyses.
Keywords: zlitine-Al; obdelave visokohitrostne; integriteta površin; hrapavost površin; mikrotrdota; aluminijeve zlitine; aluminium alloy; preiskava materiala; površinske lastnosti; trdota; hrapavost